2020
DOI: 10.1002/vzj2.20054
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, irrigation, and alley management effects on nitrate leaching from raspberry

Abstract: High NO 3 concentrations in the Abbotsford-Sumas aquifer are linked to raspberry (Rubus idaeus L.) production. Passive capillary wick samplers were used to quantify the impacts of N, irrigation, and alley managements on drainage and NO 3 leaching from raspberry rows and alleys over 4 yr. Conventional management (100 kg N ha −1 surface broadcast on the row as a split application, clean cultivation of alleys, and fixed-duration drip irrigation) was compared with different mineral fertilizer N rates, N applied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Despite addition of lower amounts of water, and thus lower N inputs through N‐laden irrigation water under ET‐scheduled than fixed‐duration irrigation (28 vs. 60 kg N ha −1 ), there was no difference in berry yield, crop vigor, or crop N status between the I ET and N 100 treatments. Whereas there was no significant difference in soil NO 3 –N concentration measured in the row between the I ET and N 100 treatments, the N 100 treatment had significantly greater NO 3 leaching during the growing season compared with the I ET treatment (Kuchta et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite addition of lower amounts of water, and thus lower N inputs through N‐laden irrigation water under ET‐scheduled than fixed‐duration irrigation (28 vs. 60 kg N ha −1 ), there was no difference in berry yield, crop vigor, or crop N status between the I ET and N 100 treatments. Whereas there was no significant difference in soil NO 3 –N concentration measured in the row between the I ET and N 100 treatments, the N 100 treatment had significantly greater NO 3 leaching during the growing season compared with the I ET treatment (Kuchta et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Water management can also influence N cycling; insufficient water supply limits crop growth and excess water contributes to NO 3 leaching (Neilsen and Neilsen, 2019). There is evidence of NO 3 leaching from the raspberry root zone over the growing season in response to irrigation in this region (Kuchta et al, 2020;Loo, Zebarth, Ryan, Forge, & Cey, 2019). Irrigation scheduling based on evaporative demand may provide a means to improve water and nutrient management and promote water conservation (Neilsen and Neilsen, 2002) relative to the current practice of fixed-duration irrigation management.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been widely observed that the variation and intensity of precipitation are one of the most important factors governing nitrate leaching (e.g., Di and Cameron, 2002;Jabloun et al, 2015;He et al, 2018). Nitrogen in groundwater, especially in an unconfined aquifer, is a direct response to nitrogen leaching from the vadose zone (Hansen et al, 2017;Kuchta et al, 2020). Petrovic (1990) found that there is a great potential for nitrate leaching under increased precipitation in the late fall due to reduced evapotranspiration and decreased microbial activity.…”
Section: Discussionmentioning
confidence: 99%